Pengaruh Iklan Media Elekteronik dan Word Of Mouth Terhadap Keputusan Pembelian Konsumen - Khoirul Rizal Ramadhani (BIMA : Journal of Business and Innovation Management, 2019)
This research aims to test and analyse influences. Electronic media advertisements and word of Wouth against consumer purchase decisions (case study of Traveloka users Faculty of Economics University of Hasyim Asy’ari) data collection methods using questionnaires and analytical techniques used are Multiple linear regression in 125 students of the economics Faculty of Universitas Hasyim Asyari of Traveloka users. The analysis of data on this study uses SPSS help version 23. The sampling techniques used are purposive sampling and the data testing techniques used in this study include validity tests with correlation between scores, reliability tests with Cronbach Alpha. Test classic assumptions and multiple liner regression analyses, to test and prove the research hypothesis. The results of T-Test (partial) studies show that electronic media ad variables (X1) have an insignificant positive influence on Traveloka (Y) Purchase decisions and word of mouth (X2) ad variables have an insignificant positive influence Decision to purchase the Traveloka (Y). The results of F test Research (simultaneous) show the results that the electronic media ads and word of mouth overall are of simultaneous and significant effect on the purchase decision of Traveloka (Y).